Comparison of clinical outcome of laparoscopic versus open appendectomy, single center experience. Issue 5 (May 2018) - Shimoda, Mitsugi; Maruyama, Tsunehiko; Nishida, Kiyotaka; Suzuki, Kazuomi; Tago, Tomoya; Shimazaki, Jiro; Suzuki, Shuji
Abstract: Introduction: Laparoscopic appendectomy (LA) is now a treatment of choice in patients with appendicitis. This study compares the treatment outcomes of LA and open appendectomies (OA) in our department. Patients and Methods: From January 2006 to April 2016 a total of 185 patients underwent appendectomy at our institution. We divided the patients into two groups; LA group (LAG) and OA group (OAG). Following parameters were analyzed: age, gender, preoperative clinicolaboratory characteristics, operative factors, interval appendectomy, length of hospital stay (LHS), and surgical site infections (SSI). Results: There were 93 patients in LA G and 92 in OAG. According to the Univariate analysis, there were statistically significant differences among age (p = 0.037), LHS (p = 0.0001), duration till resuming oral intake (p = 0.016), blood loss (p = 0.038), SSI ratio (p = 0.044) and CRP level (p = 0.038) between the LAG and the OAG. According to the Multivariate analysis, blood loss (p = 0.038) and LHS (p = 0.023) were significantly different between both groups. Conclusion: LA was decreasing blood loss and LHS.